An e-Learning Environment Based on the Moodle Platform for Iraq Universities - Muayed S AL-Huseiny (Wasit Journal of Engineering Sciences)
This paper proposes the deployment of learning management systems to provide virtual environment to higher education in Iraq. In this paper we show that implementing a learning management system (LMS) to manage learning process is within reach even with little material and human resources. This paper proposes an open source popular and free of charge platform called Moodle. We also show that other solutions such as web-based alternatives to LMS are completely unaffordable given the limited financial resources of our universities. The system is aimed for use by university level students and educators (teachers and instructors). Further, a deployment plan is given in this paper to provide a guidance and reference for the implementation requirements and steps of this LMS operation.